Two-Way Assessment of Ionospheric Maps Performance Over the Brazilian Region: Global Versus Regional Products - Jerez, Gabriel O. [UNESP]; Hernández-Pajares, Manuel; Goss, Andreas; Prol, Fabricio S.; Alves, Daniele B. M. [UNESP]; Monico, João F. G. [UNESP]; Schmidt, Michael (American Geophysical Union (AGU), 2023)
Vertical total electron content (VTEC) has great importance in describing the ionosphere. VTEC values are commonly distributed in regular grids by means of so-called global ionospheric maps (GIMs) and regional ionospheric maps (RIMs). Although considerable research has been conducted to develop regional and global models, there is no clear understanding of the benefits of using RIMs over GIMs. Aiming to contribute to this discussion, our investigation presents a comparison between seven global and regional ionospheric maps considering two approaches: (a) ionosonde data-based assessment and (b) global navigation satellite systems (GNSS) positioning assessment. A challenging low latitude ionosphere scenario, the Brazilian region, was selected during a week with an active geomagnetic storm. The assessment results with ionosonde data have shown better performance of the RIM products named OTHR and OTRG. Among the global products, CODG and UQRG have shown the best performances. The worst results were obtained with the RIM named Instituto Nacional de Pesquisas Espaciais. The assessment with GNSS positioning led to larger and noisier errors close to the equatorial anomaly. Two of the analyzed RIMs presented expected large errors in stations at the edges of the coverage area. To overcome this issue, a hybrid product was proposed to extend the RIM covered region. The proposed hybrid product (OTRG) presented the best results in the GNSS positioning domain.
Keywords: equatorial region; global ionospheric maps; GNSS; ionosonde; ionosphere; regional ionospheric maps